Visual Speech Perception Cues Constrain Patterns of Articulatory Variation and Sound Change - Havenhill, Jonathan; Do, Youngah (Frontiers in Psychology, 2018)
What are the factors that contribute to (or inhibit) diachronic sound change? While acoustically motivated sound changes are well documented, research on the articulatory and audiovisual-perceptual aspects of sound change is limited. This paper investigates the interaction of articulatory variation and audiovisual speech perception in the Northern Cities Vowel Shift (NCVS), a pattern of sound change observed in the Great Lakes region of the United States. We focus specifically on the maintenance of the contrast between the vowels /ɑ/ and /ɔ/, both of which are fronted as a result of the NCVS. We present results from two experiments designed to test how the NCVS is produced and perceived. In the first experiment, we present data from an articulatory and acoustic analysis of the production of fronted /ɑ/ and /ɔ/. We find that some speakers distinguish /ɔ/ from /ɑ/ with a combination of both tongue position and lip rounding, while others do so using either tongue position or lip rounding alone. For speakers who distinguish /ɔ/ from /ɑ/ along only one articulatory dimension, /ɑ/ and /ɔ/ are acoustically more similar than for speakers who produce multiple articulatory distinctions. While all three groups of speakers maintain some degree of acoustic contrast between the vowels, the question is raised as to whether these articulatory strategies differ in their perceptibility. In the perception experiment, we test the hypothesis that visual speech cues play a role in maintaining contrast between the two sounds. The results of this experiment suggest that articulatory configurations in which /ɔ/ is produced with unround lips are perceptually weaker than those in which /ɔ/ is produced with rounding, even though these configurations result in acoustically similar output. We argue that these findings have implications for theories of sound change and variation in at least two respects: 1) visual cues can shape phonological systems through misperception-based sound change, and 2) phonological systems may be optimized not only for auditory but also for visual perceptibility.